Characterization of polysaccharides extracted from spent coffee grounds by alkali pretreatment - Ballesteros, Lina F. (2015)
Spent coffee grounds (SCG), obtained during the processing of coffee powder with hot water to make soluble coffee, are the main coffee industry residues and retain approx. seventy percent of the polysaccharides present in the roasted coffee beans. The purpose of this study was to extract polysaccharides from SCG by using an alkali pretreatment with sodium hydroxide at 25 °C, and determine the chemical composition, as well as the antioxidant and antimicrobial properties of the extracted polysaccharides. Galactose (60.27% mol) was the dominant sugar in the recovered polysaccharides, followed by arabinose (19.93% mol), glucose (15.37% mol) and mannose (4.43% mol). SCG polysaccharides were thermostable, and presented a typical carbohydrate pattern. Additionally, they showed good antioxidant activity through different methods and presented high antimicrobial percent inhibition against Phoma violacea and Cladosporium cladosporioides (41.27% and 54.60%, respectively). These findings allow identifying possible applications for these polysaccharides in the food industry.